Electrochemical control of [FeFe]-hydrogenase single crystals reveals complex redox populations at the catalytic site. Issue 36 (19th August 2021) - Morra, Simone; Duan, Jifu; Winkler, Martin; Ash, Philip A.; Happe, Thomas; Vincent, Kylie A.
Abstract : The distribution of redox species in single crystals of [FeFe]-hydrogenase can be tuned electrochemically. All catalytic intermediates are observed by simultaneous infrared microspectroscopy, providing a roadmap for enriching specific redox states. Abstract : Elucidating the distribution of intermediates at the active site of redox metalloenzymes is vital to understanding their highly efficient catalysis. Here we demonstrate that it is possible to generate, and detect, the key catalytic redox states of an [FeFe]-hydrogenase in a protein crystal. Individual crystals of the prototypical [FeFe]-hydrogenase I from Clostridium pasteurianum (CpI) are maintained under electrochemical control, allowing for precise tuning of the redox potential, while the crystal is simultaneously probed via Fourier Transform Infrared (FTIR) microspectroscopy. The high signal/noise spectra reveal potential-dependent variation in the distribution of redox states at the active site (H-cluster) according to state-specific vibrational bands from the endogeneous CO and CN − ligands. CpI crystals are shown to populate the same H-cluster states as those detected in solution, including the oxidised species Hox, the reduced species Hred/HredH +, the super-reduced HsredH + and the hydride species Hhyd. The high sensitivity and precise redox control offered by this approach also facilitates the detection and characterisation of low abundance species that only accumulate within a narrow window of conditions, revealing new redox intermediates.